Establishment of tissue culture protocols for Curculigo latifolia dryand and determination of uniformity among plantlets using SSR markers - Babaei, Nahid (2012)
Curculin found in Curculigo latifolia fruit has great potential for the pharmaceutical industry. Studies were conducted with the objectives of establishing a tissue culture protocol for C. latifolia and to determine uniformity among plantlets and their mother plants using SSR markers. Although the plants are found abundantly in Malaysia, commercial fruit production from superior varieties is at the early stage. Propagation through seeds and rhizomes are poor and planting using materials harvested directly from the forest is precarious as the genetics of this plant is understudied. Therefore tissue culture provides the means of producing true to type and uniform seedlings in mass numbers. Plants were collected from Jelebu, Negeri Sembilan and maintained under 70% shade with regular watering for at least six months. Petioles and shoot tips were used as explants but this resulted in very high in vitro contamination. Therefore, a sterilization protocol suitable for C. latifolia was developed. Sterilization and browning elimination were performed by pre-treatment with different antioxidants (citric acid, ascorbic acid and PVP (0.1%)), fungicide (bavistin 0.1%), and antibiotic (chloramphinicol 0.1%) on an orbital shaker for 9 hours followed by disinfecting with mercuric chloride (0.1%) for 5 minutes with 62.5% of shoot tips and 100% survival of explants after 45 days of culture. Petiole explants resulted in a higher percentage of explant (83.3%); however, there was more necrosis than with shoot tips, and there was a lower percentage of explant survival (49.2%). Thus, shoot tips were preferred for use as explants for regeneration. The direct regeneration of shoots from explants were optimized using Murashige and Skoog (1962) medium supplemented with different concentrations of single thidiazuron (TDZ) treatment (0, 0.5, 1, 1.5, 2 mgl-1) or in combination with IBA (0, 0.25, 0.5 mgl-1). The best results in terms of percentage of regeneration (77.8% and 83.3%), number of shoots (3.08 and 7.52) and shoot length (1.43 and 2.71 cm) were from treatment consisting of 0.5 mgl-1 TDZ and 0.25 mgl-1 after 10 and 14 weeks of culture, respectively. Meristems were elongated and roots were induced to generate a single plant in the control treatment. In this study it was also observed that a single concentration of 2 mgl-1 TDZ produced the highest percentage of scalp induction (77.8%). Scalp induction from shoot tip explants on MS medium with different concentrations of TDZ (0, 1, 2, 3, 4 mgl-1) showed that TDZ at a concentration of 3 mgl-1 was the best treatment for percentage of scalp induction (83.3%). In determining the growth pattern and best time for sub-culturing, the scalp weighing 1.1 ± 0.02 g was transferred onto MS medium containing 3 mgl-1 TDZ. This confirmed that four weeks interval was the best time for scalp sub-culturing. Scalp maintenance studies were performed on MS medium supplemented with different concentration of TDZ (0, 1, 2, 3, 4 mgl-1) with sub-culturing at four week intervals for three subcultures. The results indicated that 3 mgl-1 was the best concentration of TDZ for scalp maintenance (5.91 g) and the highest growth index (4.91) was obtained after the third subculture. Root induction and elongation studies were performed by separating regenerated shoots longer than 2 cm and culturing onto MS medium supplemented with different concentrations of IBA (0, 0.25, 0.5, 0.75 mgl-1). Shoots sub-cultured every four weeks showed that MS medium devoid of plant growth regulators was the best treatment for percentage root induction (86.7%) and root length (4.87 cm), but IBA at a concentration of 0.25 mgl-1 induced more roots (7.64) after eight weeks of culture. SSR markers were developed using 3′ and 5′ anchored ISSR markers. Amplified PCR products were ligated into vector and transformed into E.coli after purification. The positive clones were sequenced and SSR primers were designed using the PRIMER3 software (http:// www.genome.wi.mit.edu/cgibin/ primer/primer3.cgi). These primers were tested on 12 accessions of wild C. latifolia collected from all states of Peninsular Malaysia. From the 33 designed SSR primers, 22 primers were able to amplify C. latifolia target DNA and 11 primer pairs were polymorphic. The number of observed alleles (Na) per locus ranged from three to six. The allele size was between 141 and 306 bp. The observed heterozygosity ranged from 0.00 to 0.37, whereas the expected heterozygosity ranged from 0.52 to 0.81. The polymorphic information content (PIC) value of each locus was between 0.59 and 0.81, with an average of 0.67 showing that the primers were highly polymorphic. Genetic variations observed in the mother plants when they were analyzed using the 11 primers. Plantlets from in vitro cultures showed the same allele sizes when compared to their mother plants and generic uniformity was observed among the plantlets. Plantlets reached 2.5 cm in height before separation from explants and sub-culturing thus avoiding somaclonal variations. The plantlets were then prepared for acclimatization and transfered to the nursery. This study demonstrated a new breakthrough for producing uniform plantlets from in vitro cultures for C.latifolia. It established a sterilization technique, optimal conditions for direct and indirect regeneration of uniform plantlets and finally provided a means of producing seedlings from superior hybrids with desirable fruits.